A educação no primeiro governo de Lauro Sodré (1886-1897): os sentidos de uma concepção político-educacional republicana - MORAES, Felipe Tavares de (Universidade Federal do Pará, 2012)
This work has the theme History of Education and has as its object of research to design educational policy-oriented educational reforms of the first government of Lauro Sodré (1891-1897). Its goal is to analyze the meanings that this concept has assumed in political and educational leadership by those educational reforms - a view that this conception is formulated originally in the Provisional Government (1889-1891), chaired by Justo Chermont, prior to Lauro Sodré. It problematizes the goals and objectives that the design constructed in the politico-educational Provisional Government (1889-1891) takes the reforms mentioned above, ie, what the senses, political and educational, this conception will toward these educational reforms of the first government Lauro Sodré (1891-1897). As a methodology, research documents, using primary sources (documents) and secondary (history), and its articulation with the theoretical. So point the documentary corpus used. It was divided into three categories: official printed documents, newspaper and printed works. Among the official printed documents: Reports and Messages from the President of the Province from 1886 to 1889 and Governor of the State (Lauro Sodré) to Congress on the State of Pará, in the period 1891-1897. The Journal: The Republic between 1886-1897. And finally, the printed works: works of Lauro Sodré, as beliefs and opinions (1997) and Words and acts (1896). For this effort, we used as a theoretical object for reading the proposed here: the concept of organic intellectual Antonio Gramsci (1989, 2001); speech according to Mikhail Bakhtin (1979); educational field in the formulations of Pierre Bourdieu (1982;2003, 2008) and representation according to Roger Chartier (1990, 1991). It was found that the design political-educational investigation has its origins in proposals and criticisms of Republican policy and education in the Empire. These propositions are effective in reforming the primary education of the Provisional Government, the purpose of education, and training of citizens committed to regenerate and the newly proclaimed republican regime, from childhood, as political purpose. In the reforms of government operated in the first Lauro Sodré, the concern is with secondary education and vocational training as well as citizens with workers Para. Thus, we conclude that this political conception of education seeks to legitimize the republican regime in its early stages and the time of its consolidation, seeking, through education, targeting their political intentions.